2006
DOI: 10.1038/ni1375
|View full text |Cite
|
Sign up to set email alerts
|

Interleukin 27 limits autoimmune encephalomyelitis by suppressing the development of interleukin 17–producing T cells

Abstract: Interleukin 27 (IL-27) was first characterized as a proinflammatory cytokine with T helper type 1-inducing activity. However, subsequent work has demonstrated that mice deficient in IL-27 receptor (IL-27R alpha) show exacerbated inflammatory responses to a variety of challenges, suggesting that IL-27 has important immunoregulatory functions in vivo. Here we demonstrate that IL-27R alpha-deficient mice were hypersusceptible to experimental autoimmune encephalomyelitis and generated more IL-17-producing T helper… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

39
754
5
11

Year Published

2007
2007
2014
2014

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 757 publications
(809 citation statements)
references
References 44 publications
39
754
5
11
Order By: Relevance
“…9A and B). Consistent with these data, Ghilardi and colleagues [22] reported that IL-27 specifically suppressed IL-6-induced proliferation of CD4 + CD25 -effector but not regulatory T cells. Thus, the enhanced IL-17 expression in EBI3 -/-mice is unlikely due to an inhibition of the population of Foxp3 + CD25 + regulatory T cells.…”
Section: Ebi3 -/-Mice Are Resistant To L Monocytogenes Infectionmentioning
confidence: 54%
See 3 more Smart Citations
“…9A and B). Consistent with these data, Ghilardi and colleagues [22] reported that IL-27 specifically suppressed IL-6-induced proliferation of CD4 + CD25 -effector but not regulatory T cells. Thus, the enhanced IL-17 expression in EBI3 -/-mice is unlikely due to an inhibition of the population of Foxp3 + CD25 + regulatory T cells.…”
Section: Ebi3 -/-Mice Are Resistant To L Monocytogenes Infectionmentioning
confidence: 54%
“…IL-27Ra-deficient mice studies indicate that IL-27 negatively regulates the development of Th17 cells [22,23]. However, there is no IL-27 (EBI3 or p28) deficiency study to directly prove the role of IL-27 on the regulation of IL-17 and Th17 cells.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…42,44,114,129 The anti-inflammatory effects of IL-27 are highlighted by the development of exaggerated Th17 immunity and severe EAE by IL-27 receptor alpha (IL-27Ra)-deficient mice. 130 IL-27 is produced by innate cells in response to TLR activation, by a mechanism that involves the autocrine effects of IFN-b. 131,132 As exogenous IFN-b triggers IL-27 production by cells of the innate immune system including DCs, 133 it has been proposed that the beneficial effects of IFN-b treatment in RRMS involve the induction of IL-27 synthesis and its effects on Tr1 and Th17 cell differentiation.…”
Section: Regulation Of DC Function By Il-27mentioning
confidence: 99%